2008
DOI: 10.2172/938581
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vadose Zone Sediments Below the TX Tank Farm: Boreholes C3830, C3831, C3832 and RCRA Borehole 299-W10-27

Abstract: This report was revised in September 2008 to remove acid-extractable sodium data from Tables 4. 8, 4.28,4.43, and 4.59. The sodium data was removed due to potential contamination introduced during the acid extraction process. The rest of the text remains unchanged from the original report issued in April 2004.The overall goal of the Tank Farm Vadose Zone Project, led by CH2M HILL Hanford Group, Inc., is to define risks from past and future single-shell tank farm activities at Hanford. To meet this goal, CH2M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(58 citation statements)
references
References 31 publications
(72 reference statements)
5
53
0
Order By: Relevance
“…The average amount of organic carbon in sediments collected from the background borehole (C33991) was 0.06% by weight (Lindenmeier et al 2003), while the average for all of the 241-B Tank Farm direct-push samples was 0.08% by weight. Inorganic carbon, as CaCO 3, was also present at concentrations that are typical for Hanford formation sediments (0.3 to 1.5 wt% as CaCO 3 ) and compared well with other Hanford formation samples (Lindenmeier et al 2003;Serne et al 2004a;Brown et al 2006). …”
Section: Total Carbon Calcium Carbonate and Organic Carbon Content supporting
confidence: 68%
“…The average amount of organic carbon in sediments collected from the background borehole (C33991) was 0.06% by weight (Lindenmeier et al 2003), while the average for all of the 241-B Tank Farm direct-push samples was 0.08% by weight. Inorganic carbon, as CaCO 3, was also present at concentrations that are typical for Hanford formation sediments (0.3 to 1.5 wt% as CaCO 3 ) and compared well with other Hanford formation samples (Lindenmeier et al 2003;Serne et al 2004a;Brown et al 2006). …”
Section: Total Carbon Calcium Carbonate and Organic Carbon Content supporting
confidence: 68%
“…We also have found that bulk elemental analysis of moderately radionuclide-contaminated sediments, such as the three TX borehole samples, do not vary significantly from uncontaminated samples (Serne et al 2004). …”
Section: Elemental Analysismentioning
confidence: 65%
“…The first PNNL report (Serne et al 2004) discussed the characterization of 1) uncontaminated sediment from a Resource Conservation and Recovery Act (RCRA) borehole (299-W10-27) that provides baseline data to compare against information from contaminated sediment; and 2) contaminated sediment obtained from three boreholes near tanks TX-104, TX-105, and TX-107. The two documents contain preliminary interpretations to identify the distribution of key contaminants within the vadose zone and to determine what their future migration potential could be.…”
Section: Introductionmentioning
confidence: 99%
“…In the top 30 m of the boreholes, matric potential values ranged from −0.002 to −0.14 MPa, with an overall average of −0.02. Such high values are indicative of draining conditions relative to the water table location at 78 m. Serne et al (2004a) provided some chloride data from borehole 299-W10-27 located about 10 m (30 ft) outside the east fence of WMA TY. The borehole was installed between January and March 2001.…”
Section: B322 Pnnl-14121mentioning
confidence: 99%
“…Pore water chloride data are presented in Serne et al (2004a) Table B.12 gives the pore water chloride concentrations for boreholes C3830, C3831, and C3832. Pore water chloride concentration profiles for boreholes C3830,C3831,and C3832 are presented in Figures B.17,B.18,and B.19,respectively.…”
Section: B333 Pnnl-14594mentioning
confidence: 99%